Maybe It's Not the Meth: Considering Biopsychosocial Contributors to Cognitive Impairment in Methamphetamine Polydrug Use - Gooden, James R.; Petersen, Vanessa; Bolt, Georgia L.; Curtis, Ashlee; Manning, Victoria; Cox, Catherine A.; Lubman, Dan I.; Arunogiri, Shalini (Frontiers in Psychiatry, 2022)
Objective: In considering the cognitive harms of methamphetamine (MA) use, there is currently a limited appreciation of the profile of pre-existing, comorbid, or modifiable risk factors for cognitive impairment in individuals with MA-polydrug use who present to clinical services. This is in contrast to the well-recognised evidence in alcohol use groups. The aim of this study was to investigate the biopsychosocial and neuropsychological profiles of MA-polysubstance using individuals reporting cognitive impairment in comparison to an alcohol-using group. Methods: A retrospective file audit was undertaken of individuals who presented for assessment to a specialist addiction neuropsychology service and reported either more than one year of heavy MA use as part of a polydrug use history (n=40) or having only used alcohol (n=27). Clinical histories including demographic, medical, mental health, substance use, and neuropsychological assessment results were extracted from medical records. Between group comparisons were conducted to explore differences in the MA-polydrug versus the alcohol group. Results: Individuals in the MA-polydrug group were significantly younger commenced substance use at an earlier age, were more likely to have an offending history, and experienced an overdose than those in the alcohol group. No differences in comorbid neurodevelopmental, psychiatric or acquired brain injury diagnoses were observed between groups. For neuropsychological functioning, significant group differences were observed in overall IQ, semantic verbal fluency, and psychomotor tracking, where individuals in the alcohol group performed significantly worse. Conclusions: Neuropsychological profiles were largely equivalent between groups across cognitive domains, with minor differences in favour of the MA-polydrug group. Relative to the general population, cognitive functioning was reduced for both groups across a range of domains. High rates of comorbid mental health concerns were common across both groups, however, individuals in the MA-polydrug group presented with a higher risk of overall harm from substance use at a significantly younger age which is a unique concern for this group. These findings highlight the importance of considering the biopsychosocial factors, such as age of first use, emotional distress, indirect substance related harms including overdose and blood born virus infection that may be relevant to experiences of cognitive difficulty in MA-polydrug users.